STUDI EKSPLORATIF BAHAN AJAR CELLO BERBASIS METODE SUZUKI - NANDYA ABROR NURMUSABIH; HARI MARTOPO; AYU TRESNA YUNITA (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2018)
Suzuki method is a method of learning that emphasizes the importance of music education musical talent as early as possible for children to use the native language (mother tongue). This method is widely misunderstood by the public simply by using a curriculum book, without applying the philosophy of its creator, Shinici Suzuki is educated with affection Nurtured by Love and his theory that Talent Education.The Suzuki Method exploration objectives are: (1) to enrich the teaching materials cello-based Suzuki Cello Method using exploratory method which the research methods used to study the unknown, not yet understood, and not recognized properly, (2) to promote the Suzuki Method in learning the cello. The conclusions are: (1) the enrichment of teaching material cello using the Suzuki Method exploratory method, (2) exploratory method is applied to the enrichment of cello teaching materials as an attempt to socialize the Suzuki Method.